Authority Vis-à-vis Scientific Logic: A Critique of the Epistemological Foundations of Fiqh - Reza Fauzi Nazar; Dudang Gojali; Abdul Haris Citra Atmaja (The Institute of Research and Service Community IPMAFA Pati, 2025)
This paper explores the epistemological problem of Islamic jurisprudence (fiqh), which is often celebrated for its flexibility. The main question addressed is why fiqh continues to survive despite its weak logical structure when measured against the standards of formal logic. Positioned within the framework of philosophy of science and mantiq (logic), this study argues that the resilience of fiqh does not stem from logical consistency but rather from its role as an authoritative system. The analysis focuses on three critical aspects: the definitional ambiguity of key concepts that fail to fulfill the criterion of jāmi‘ wa māni’, the analogical reasoning (qiyās) that frequently relies on assumed causality instead of demonstrative proofs (burhān), and the legal maxims (qawā‘id al-fiqhiyyah) that tend to operate as post-decision justifications rather than guiding principles of reasoning. These weaknesses indicate that fiqh is closer to a system of authority than to a discipline of science in the strict sense. Nevertheless, the same weaknesses paradoxically contribute to its adaptability and persistence across different eras. The paper concludes that fiqh is strong in praxis but fragile in theory, and it recommends an epistemological reconstruction through precise definitional work, strengthening qiyās with demonstrative causality, and reformulating legal maxims with objective parameters. Such reconstruction would enable fiqh to transform from a primarily authoritative tradition into a rational, systematic, and contextually relevant body of knowledge.